Corrigendum: a momentum form of Kane's equations for scleronomic systems. Issue 4 (4th July 2018) - Phillips, James R.; Amirouche, Farid
ABSTRACT: In the authors' previously published paper, 'A Momentum form of Kane's equations for scleronomic systems' (https://doi.org/10.1080/13873954.2017.1385638 ), the discussion defining the procedure for calculating nonworking constraint forces is flawed. In this corrigendum, we supply a corrected discussion and procedure, illustrated with an example.